El impacto del modelo extractivista en la cosmovisión indígena del territorio - Limardo, Camila González (Universidad Nacional del Litoral, 2021)
Through case analysis, this paper addresses the anthropocentric eurocentric position, legitimizing the extractivist model, and an approach to the holistic worldview of indigenous communities.